Ovule-gall stimulating a large fake fruit on Miconia chamissois Naudin (Melastomataceae): a structural overview - Bomfim, Phabliny M.S; Kuster, Vinícius C; Caetano, Ana Paula S; Gonçalves, Letícia A; Oliveira, Denis C (Botany, 2021)
The developmental processes of galls are better known when they are induced on vegetative organs, whereas they have hardly ever been described for reproductive ones. Herein, galls induced by Allorhogas uberlandiensis (Hymenoptera) on ovules of Miconia chamissois Naudin (Melastomataceae) were analyzed in terms of morphological, anatomical, histochemical, and cytological characteristics. Galls are induced on the ovules before fertilization, and act as a physiological seed. Therefore, the ovary grows and develops into a fruit-like gall. The ovule-galls are on average 20-times larger than the seeds, and fruit-like gall volume is on average 5.4-times greater than that of mature fruits. These are related to cell hypertrophy and tissue hyperplasia in the host organ. There is a typical nutritive-tissue formation in the ovule-gall with lipid, protein, and pectin storage, as well as a storage tissue close to the epidermis. This nutritive tissue shows a smooth endoplasmic reticulum, multivesicular bodies, and mitochondria-rich cells. After gall induction, all of the ovules degenerate, and the ovary and hypanthium hypertrophy to form the fruit-like gall. The fruit-like galls form a physical barrier blocking the anthesis, thereby preventing fertilization and keeping only ovule-galls. Our study shows that the galling insect A. uberlandensis may reduce the reproductive success of M. chamissois, thus acting as a biological control agent for this host-plant population.